1976
DOI: 10.1126/science.816006
|View full text |Cite
|
Sign up to set email alerts
|

X- and Y-Cells in the Dorsal Lateral Geniculate Nucleus of the Owl Monkey ( Aotus trivirgatus )

Abstract: The owl monkey, as do other mammals, has X-and Y-cells in its lateral geniculate nucleus. X-cells are found in the parvocellular laminae; Y-cells, in the magnocellular laminae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 12 publications
(6 reference statements)
6
99
0
Order By: Relevance
“…form), while Y and W types would analyze movement [56,57]. Although most of this work has been carried out in the cat, a similar dichotomy is thought to exist in the monkey [58,59]. In contrast to the cat, it seems that in the monkey, the X and Y systems are morphologically segregated at the LGd level, the magnocellular layers constituting the Y system, and the parvocellular layers, the X system [59].…”
Section: Genieulo-cortical Pathwaymentioning
confidence: 96%
“…form), while Y and W types would analyze movement [56,57]. Although most of this work has been carried out in the cat, a similar dichotomy is thought to exist in the monkey [58,59]. In contrast to the cat, it seems that in the monkey, the X and Y systems are morphologically segregated at the LGd level, the magnocellular layers constituting the Y system, and the parvocellular layers, the X system [59].…”
Section: Genieulo-cortical Pathwaymentioning
confidence: 96%
“…Both techniques yielded satisfactory results. However, the latter provided direct identification of thalamic afferents and in addition enabled us to distinquish parvoand magnocellular afferents from one another on the basis of receptive field organization (Wiesel and Hubel, 1966;Sherman et al, 1976;Dreher et al, 1977;Schiller and Malpeli, 1978;Lee et al, 1979). These studies have been reported briefly (Blasdel et al, 1981;Blasdel and Lund, 1982a, b).…”
mentioning
confidence: 99%
“…Our criteria for classifying and distinguishing parvocellular responses from those of the magnocellular laminae are those of Wiesel and Hubel (1966) several more recent observations (Sherman et al, 1976; with the aid of a Leitz Dialux microscope linked to an Dreher et al, 1977;Lennie and Derrington, 1981;Shapley LSI-11 computer, color video monitor, and graphics diget al, 1981;Marrocco et al, 1982). On the basis of these itizer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The feedforward, dual-channel architecture explains masking as a function of time between target and mask onsets and/or offsets. Both offsets and onsets activate the faster transient channel, which inhibits the slower sustained channel carrying information about stimulus identity (the transient/sustained maps onto the magnocellular/parvocellular distinction; Sherman, Wilson, Kaas, & Webb, 1976). In metacontrast masking, the sustained activity representing the target is inhibited by the rapid mask-induced transient when the mask onsets 50-100 ms after the target.…”
Section: Theories Of Osmmentioning
confidence: 99%